Factors that enable breakthroughs in tennis: A case study of elite college tennis players in Japan - Hioki, K.; Hotta, S.; Iba, T. (Coaching and Sport Science Review, 2024)
In the world of sports, the phenomenon of a dramatic improvement in competition results at some point is called a "breakthrough." In this study, "breakthrough" is defined as "a dramatic improvement in competition results at some point," and the purpose of this study is to reveal hypothetical findings on the factors that enable "breakthroughs" in tennis. Semi-structured interviews were conducted with eight Japanese college tennis players who had experienced a "breakthrough" in the past, and who had records of being in the top 8 or above in national championships. The interview content was transcribed and used to conduct a qualitative analysis. As a result, the following three hypothetical findings were revealed: "maintaining high motivation," "continuous growth," and "high performance during games" are important for enabling "breakthroughs" in tennis. Those hypothetical findings will be useful information for athletes who are aiming for "breakthroughs" and for coaches who support them.